A Body shape index significantly predicts MRI-defined abdominal adipose tissue depots in non-obese Asian Indians with type 2 diabetes mellitus. Issue 1 (13th October 2020) - Anoop, Shajith; Krakauer, Jesse; Krakauer, Nir; Misra, Anoop
Abstract : Introduction: We aimed to determine the correlations of volumes of subcutaneous abdominal adipose tissue (SCAT) (anterior, posterior, superficial and deep), total SCAT, intraperitoneal adipose tissue, retroperitoneal abdominal adipose tissue (RPAT), total intra-abdominal adipose tissue (IAAT), pancreatic volume, liver span, total body fat (TBF) and truncal fat mass (TFM) with anthropometric indices, viz., A Body Shape Index (ABSI), Hip Index, their Z scores and Anthropometric Risk Index in non-obese (body mass index (BMI) <25 kg/m 2 ) Asian Indians with type 2 diabetes mellitus (T2DM). Research design and methods: Non-obese patients with T2DM (cases; n, 85) and BMI-matched, healthy subjects (controls; n, 38) underwent anthropometry, dual energy X ray absorptiometry (DXA) for estimation of TBF, TFM and 1.5 T MRI for estimation of volumes of abdominal adipose tissue depots, pancreas and liver span. Spearman's correlation analysis and Receiver Operator Characteristic curve analysis were applied. Results: The Z score of ABSI (Z_ABSI) showed significantly positive correlation with volumes of all depots of abdominal SCAT, total IAAT and RPAT in cases. Area under the curve for Z_ABSI (0.87) showed higher sensitivity: 82.0 %, specificity: 81.5 %, at a predictive cut-off value of 0.49 for abdominal adiposity. Conclusion: In non-obese Asian Indians with T2DM, the Z_ABSI showed significant correlation with IAAT and SCAT and higher predictive accuracy for abdominal adiposity. Highlights of the study: This is the first MRI-based study in the context of ABSI in non-obese (BMI <25 kg/m 2 ) Asian Indians with T2DM. Findings indicate that Z_ABSI has high predictive accuracy for abdominal adiposity in non-obese Asian Indians. The Z_ABSI index showed significantly positive correlation with volumes of adipose tissue depots, viz., abdominal SCAT, total IAAT and RPAT in cases.